Investigating precipitation pattern and variability in the Niger Delta: a statistical analysis of trends and change points (1972–2022) - Ikechukwu , Mbachu (Bulletin of Geography. Physical Geography Series, 2024)
There has been significant variation in precipitation in different parts of the world, and increasingly this has been attributed to climate change. Despite reliance on rain-fed agriculture, detailed analysis of regional precipitation trends within specific sub-national areas, such as the Niger Delta, remains scant. This study examines annual rainfall trends over 51 years (1972–2022) across seven stations in the Niger Delta using different statistical methods. Descriptive statistics show different patterns among stations, some showing upward trends, others declines. Mean annual rainfall ranges from 1,969.05 mm in Akure to 2385.04 mm in Port Harcourt, showing significant regional variability. Linear regression and LOWESS analysis show mixed trends; Mann–Kendall and Spearman’s Rho tests showed significant increase in Owerri, while Sen’s slope analysis confirms varying trends across the region. Pettitt test results confirms Owerri’s significant increase in precipitation. This study contributes to a greater understanding of precipitation trends in the Niger Delta.